MAINTENANCE OF FRIESIAN HOLSTEIN COW DAIRYMANAGEMENTIN NATIONAL ANIMAL HUSBANDRY TRAINING CENTER (BBPP) BATU CITY - M. S., Resla; Miwada, I N.S.; Parimartha, i K. W. (Jurnal Peternakan Tropika, 2019)
Dairy cows are livestock commodities that have the potential to be developed. This is based on the high need for milk among the people of Indonesia. Livestock management that is applied in a livestock business is very closely related to its productivity including housing management, feeding and drinking, health and milking. Apprenticeship work practices and observations were carried out to find out the maintenance management of dairy cattle in a livestock business. Internship practice activities have been carried out at the Animal Husbandry Training Center, Batu city for two weeks from November 5-18, 2018 with Holstein Friesian dairy cattle. The method used in observing internship work practices and data collection is the method of observation, participation and interviews. The aspects studied are housing management, feeding and drinking management, health management and milk management. The observation shows that the maintenance system for Holstein Friesian dairy cattle at the Center for Animal Husbandry Training, Batu city is carried out intensively, namely by stocking livestock every day.Dairy cows are kept in cages with good maintenance management including housing management, feeding and drinking, milking and health according to the rules.Based on the results of observations it can be concluded that the dairy farming business at the Center for Animal Husbandry Training, Batu city has implemented good and appropriate maintenance management.   Keywords : maintenance management, Holstein Friesian dairy cattle.